2014
DOI: 10.1097/bte.0000000000000035
|View full text |Cite
|
Sign up to set email alerts
|

Reverse Shoulder Arthroplasty With Patient-specific Glenoid Implant Positioning Guides

Abstract: Reverse shoulder arthroplasty is the treatment of choice for rotator cuff tear arthroplasty. The success of the procedure depends largely on proper positioning and stable fixation of the glenoid component. Achieving the ideal position of the implant always remains a challenge to the operating surgeon. Various methods have been suggested to improve the initial fixation of the glenosphere intraoperatively. Even though computer navigation has shown encouraging results, it is associated with inherent difficulties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…The only other article to document the necessary time for production of the patient-specific device reported a minimum of 5 weeks 40 Table IIIPSI devices and technology used among included articlesPSI manufacturerArticle(s) citedDescriptionPSITornier–Wright MedicalGauci et al, 16 2016Walch et al, 43 2015Berhouet et al, 3 2018Four-pin peripheral supportSurgeon introduces onto glenoid.2.5-mm titanium guide wire passed through central hole.Polyamide; EOSINT P380 selective laser sintering (EOS, Krailling, Germany).Walch et al, 2015∗Materialise (Patient-Specific Shoulder Guide)Dallalana et al, 7 2016Levy et al, 27 2014Subramanya and Herald, 36 2014Heylen et al, 20 2016Removal of soft tissues from anterosuperior glenoid rim and exposure of coracoid base necessary.Guide fitted to stable position on native glenoid.Central guide pin drilled into native glenoid.Polyamide material. Selective laser sintering.Heylen et al, 2016†Zimmer Biomet (Signature Glenoid Shoulder System)Throckmorton et al, 38 2015Pietrzak, 32 2013Lau and Keith, 26 2018Throckmorton et al, 39 2014TSA: pin trajectory is neutral version and inclination.rTSA: pin trajectory is 10° of inferior tilt and neutral version.Guide applied to anterior glenoidMaterial not reported.Lau and Keith, 2018‡Custom Orthopaedic Solutions (Glenoid Intelligent Reusable Instrument System)Iannotti et al, 25 2015Iannotti et al, 23 2014Iannotti et al, 24 2017Reusable—cannulated handle over guide pin.3 or 4 adjustable peripheral legs fit on glenoid.Each leg specified leg length (1-mm increments).Legs locked by tightening collets after desired length achieved with SmartBone model (Custom Orthopaedic Solutions, Cleveland, Ohio, USA).Duocentric Group, Aston Medical (Personal Fit)Trouilloud et al, 40 2014Guide pin is passed through guide at chosen center of glenoid.Humeral component fits onto humeral head and cutting guide placed against it.Trouilloud et al, 2014§Astro Manufacturing & Design, Eastlake, OH, USA (patient-specific stereolithography devices)Hendel et al, 19 20122 instrument parts.First instrument fits on anterior glenoid.Drill guide places glenoid pin and superior guide pin; superior pin placed into base of coracoid.After glenoid...…”
Section: Resultsmentioning
confidence: 99%
“…The only other article to document the necessary time for production of the patient-specific device reported a minimum of 5 weeks 40 Table IIIPSI devices and technology used among included articlesPSI manufacturerArticle(s) citedDescriptionPSITornier–Wright MedicalGauci et al, 16 2016Walch et al, 43 2015Berhouet et al, 3 2018Four-pin peripheral supportSurgeon introduces onto glenoid.2.5-mm titanium guide wire passed through central hole.Polyamide; EOSINT P380 selective laser sintering (EOS, Krailling, Germany).Walch et al, 2015∗Materialise (Patient-Specific Shoulder Guide)Dallalana et al, 7 2016Levy et al, 27 2014Subramanya and Herald, 36 2014Heylen et al, 20 2016Removal of soft tissues from anterosuperior glenoid rim and exposure of coracoid base necessary.Guide fitted to stable position on native glenoid.Central guide pin drilled into native glenoid.Polyamide material. Selective laser sintering.Heylen et al, 2016†Zimmer Biomet (Signature Glenoid Shoulder System)Throckmorton et al, 38 2015Pietrzak, 32 2013Lau and Keith, 26 2018Throckmorton et al, 39 2014TSA: pin trajectory is neutral version and inclination.rTSA: pin trajectory is 10° of inferior tilt and neutral version.Guide applied to anterior glenoidMaterial not reported.Lau and Keith, 2018‡Custom Orthopaedic Solutions (Glenoid Intelligent Reusable Instrument System)Iannotti et al, 25 2015Iannotti et al, 23 2014Iannotti et al, 24 2017Reusable—cannulated handle over guide pin.3 or 4 adjustable peripheral legs fit on glenoid.Each leg specified leg length (1-mm increments).Legs locked by tightening collets after desired length achieved with SmartBone model (Custom Orthopaedic Solutions, Cleveland, Ohio, USA).Duocentric Group, Aston Medical (Personal Fit)Trouilloud et al, 40 2014Guide pin is passed through guide at chosen center of glenoid.Humeral component fits onto humeral head and cutting guide placed against it.Trouilloud et al, 2014§Astro Manufacturing & Design, Eastlake, OH, USA (patient-specific stereolithography devices)Hendel et al, 19 20122 instrument parts.First instrument fits on anterior glenoid.Drill guide places glenoid pin and superior guide pin; superior pin placed into base of coracoid.After glenoid...…”
Section: Resultsmentioning
confidence: 99%
“…The reported outcomes were deviation from the planning for version and inclination in all studies, from the entry point in 10 studies (five cadaveric and five clinical studies) [ 27 30 , 33 – 38 ] and from the rotation in three studies (one cadaveric and two clinical studies) [ 28 , 33 , 34 ]. Seven studies also reported the number of outliers (three cadaveric and four clinical studies) [ 28 , 29 , 31 , 32 , 36 – 38 ]. Reaming depth has never been reported.…”
Section: Resultsmentioning
confidence: 99%
“…In general, available evidence indicates that patient-specific devices improve the implantation accuracy of either the central glenoid guide pin or glenoid prosthesis based on some form of predetermined surgical plan 9, 13, 15, 20, 30. However, most published articles used patient-specific devices that were outsourced to an external manufacturer 2, 6, 8, 13, 14, 15, 22, 23, 27, 28, 30, 31, 34. Outsourcing production of patient-specific devices to external manufacturers may involve considerable expenses that could potentially exclude all but the highest-volume, highest-earning practices from benefiting from this technology.…”
Section: Discussionmentioning
confidence: 99%
“…Our power analysis determined that a sample size of 20 specimens was necessary for the purposes of this investigation, which is greater than that in the majority of available cadaveric or clinical studies investigating the impact of PSI devices on TSA 2, 9, 22, 23, 24, 27, 28, 29, 32, 34. Although it is impossible to represent the entire spectrum of TSA patients with this sample, the addition of a standard instrumentation control adds further validity that was absent in several previous investigations 2, 13, 23, 27, 32, 34.…”
Section: Discussionmentioning
confidence: 99%